Glyphosate in the production and forage quality of marandu grass - Codognoto, Luciane da Cunha; Conde, Thassiane Telles; Maltoni, Katia Luciene; Faria, Glaucia Amorim (Semina: Ciências Agrárias, 2021)
The drift of the herbicide glyphosate, used for desiccating crops or controlling weeds, can result in growth-promoting or non-target plant development effects. Thus, it is possible to use the compound to increase the biomass of forage through the hormone effect. The objective of this study was to evaluate the effects of sublethal doses of glyphosate on the production of Urochloa brizantha cv. Marandu (Marandu grass) and its nutritional quality in ruminants. The design used was completely randomized, with five replications in a factorial scheme. The treatments used were as follows: control (without glyphosate application) and four sublethal doses of glyphosate (4, 10, 14, and 20 g ha-1 of the acid equivalent). The monthly collections consisted of collecting the plant material (0.20 m) from the surface, comprising of leaves and pseudocolmos (stem and leaf sheath) to determine the dry matter production and forage chemical-bromatological parameters. The results showed that leaf/stem ratio, neutral detergent fiber, and acid detergent fiber were affected exclusively by the harvest factor. The hormone effect of the herbicide occurs in the production of dry matter and lignin in the evaluated subdoses. For crude protein, there was an interaction between the factor doses and harvest, due to the effect of glyphosate and the management applied to the harvests, showing that the sublethal doses of glyphosate promoted the production of dry matter and the food quality of Marandu grass.